Attenuated Adenylosuccinate Lyase Deficiency: A Report of One Case and a Review of the Literature - Jurecka, Agnieszka; Zikanova, Marie; Jurkiewicz, Elżbieta; Tylki-Szymańska, Anna (Neuropediatrics, 2014)
We present a 9-year follow-up of a patient with an attenuated (type II) adenylosuccinate lyase deficiency with no obvious signs of disease progression and degradation. We also review the literature, focusing on attenuated phenotype, and we report a positive effect of a ketogenic diet on seizure control. The patient presented at the age of 5 months with a history of global developmental delay. Screening of urinary purine metabolites revealed elevation of succinyladenosine and succinylaminoimidazolecarboxamide riboside (a ratio of 2:1). Mutation analysis revealed a compound heterozygosity for missense mutations: p.R426H and p.D268H. She began to walk independently at the age of 3 years. From the age of 4 years, her communication skills improved and she presented fewer autistic features. Due to poor results in seizure control, the ketogenic diet was introduced at the age of 7 years, resulting in reduction of seizure frequency. Currently, at the age of 9 years, the girl is attending a special kindergarten and is functioning very well in her preschool group. She began to make statements that form a logical continuity and make progress in simple manual operations. The patient participates in therapies such as pet therapy, hippotherapy, speech therapy, physiotherapy, hydrotherapy, and music therapy.
Keywords: adenylosuccinate lyase deficiency; genotype-phenotype analysis; ketogenic diet